Relating ionization quenching in organic plastic scintillators to basic material properties by modelling excitation density transport and amorphous track structure during proton irradiation. (28th September 2018) - Christensen, Jeppe Brage; Andersen, Claus E
Abstract: Ionization quenching in organic scintillators is usually corrected with methods that require careful assessment of the response relative to that of an ionization chamber. Here, we present a framework to compute ionization quenching correction factors (QCFs) from first principles for organic plastic scintillators exposed to ions. The tool solves the kinetic Blanc equation, of which the Birks model is a simplified solution, based on amorphous track structures models. As a consequence, ionization quenching correction factors can be calculated relying only on standard, tabulated scintillator material properties such as the density, light yield, and decay time. The tool is validated against experimentally obtained QCFs for two different organic plastic scintillators irradiated with protons with linear energy transfers (LETs) between 5– . The QCFs computed from amorphous track structure models and the BC-400 scintillator properties deviate less than 3% from the Birks model for LETs below and less than 5% for higher LETs. The agreement between experiments and the software for the BCF-12 scintillator is within 2% for LETs below and within 10% for LETs above, comparable to the experimental uncertainties. The framework is compiled into the open source software available for download. enables computations of QCFs in organic plastic scintillators exposed to ions independently of experimentally based quenching parameters in contrast to the Birks model. can improve the accuracy of correction factors and understanding of ionization quenching in scintillator dosimetry.